VARIASI PADAT PENEBARAN TERHADAP PERTUMBUHAN BENIH IKAN LELE SANGKURIANG (Clarias sp) YANG DIPELIHARA DALAM HAPA - Herliwati Herliwati (Fish Scientiae, 2016)
The aim of the research was to determine the effect of different larvae stocking density onthe growth of fish catfish cultivated in cage net. A completely randomized design wasused in this study with, 3 treatments and 3 replications. The results of this study indicate that catfish (Clarias sp) in the treatment of A (stocking density 20 larvae/m2 ) has agrowth weight, the relative lengths and feed conversion is better than treatment B (stocking density of 40 larva / m2 ) and C ( stocking density of 60 larva / m2 ). But the survival rate of the treatment A and B have better than treatment C. The results of waterquality measurement (temperature , DO, pH , NH3 and CO2 ) are still within the rangethat can be tolerated by Sangkuriang catfish (Clarias sp).